Evaluating computer-assisted memory retraining programmes for people with post-head injury amnesia. - Tam S; Man W (Brain Injury, 2004)
OBJECTIVE: The present study was designed to perform theory-driven empirical work that might contribute to a better understanding of computer-assisted training effects adopting theoretically different memory retraining strategies for people who had amnesia as a result of a brain injury. RESEARCH DESIGN: A pre-test and post-test control group quasi-experimental design was adopted to test the differences in effectiveness of four different computer-assisted memory training strategies, which were hypothesized to improve different memory skills of persons with brain injury. METHOD AND PROCEDURES: Twenty-six persons with brain injury were randomly assigned to four age- and gender-matched memory training groups (self-paced, feedback, personalized, visual presentation) and they were trained using the related computer software, evaluated by the Rivermead Behavioural Memory Test (RBMT), self-efficacy scale and built-up computer performance records. MAIN OUTCOMES AND RESULTS: All the four memory training methods showed positive among the persons with brain injury as compared with a control group, although there was no statistically significant difference among the four training methods. However, clinical improvement was found in all four methods and the Feedback group showed significant improvement in self efficacy, in comparison with the other groups. CONCLUSION: This attempt to develop and evaluate different computer applications for memory retraining was made and the effectiveness of applying customized computer technology in memory rehabilitation was critically evaluated. Results of the present study showed that the unique customized therapeutic characteristics of computer-assisted memory retraining (e.g. self-paced practice, performance feedback, salient visual presentation and personalized training contents) are positive attributes of memory skill retraining outcomes.